1993
DOI: 10.1007/bf01200730
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies of cardia carcinoma and infracardial gastric carcinoma

Abstract: In a part retrospective, part prospective study, 354 carcinomas of the cardia were compared with 1259 infracardial gastric carcinomas with regard to the age and sex of the patients, macroscopic classification, microscopic classifications, depth of invasion, and survival rates. Mortality rates are generally higher in cardia carcinoma than in stomach carcinoma. The difference is due to the significantly poorer survival of cardia carcinoma patients in stage I, while mortality rates in stages II, III, and IV of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Moreover, the frequency of HER2-positivity in the non-metastatic, potentially curative setting has not been adequately studied, yet has substantial clinical relevance, since such knowledge may guide HER2 testing for the identification of patients for HER2 targeted therapy. To date, studies in EAC have been limited by small sample sizes and inclusion of squamous cell carcinomas or subcardial gastric carcinomas whose epidemiology and biology are distinct from EAC (1719). …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the frequency of HER2-positivity in the non-metastatic, potentially curative setting has not been adequately studied, yet has substantial clinical relevance, since such knowledge may guide HER2 testing for the identification of patients for HER2 targeted therapy. To date, studies in EAC have been limited by small sample sizes and inclusion of squamous cell carcinomas or subcardial gastric carcinomas whose epidemiology and biology are distinct from EAC (1719). …”
Section: Introductionmentioning
confidence: 99%
“…All cancers in the cardiac-junctional region were of the intestinal type, as found in a German study [24]. Half of these patients had H. pylori gastritis, and only two had MAG.…”
Section: Discussionmentioning
confidence: 88%
“…Some authors have suggested that cardia carcinomas and adenocarcinomas of the esophagus share to a significantly degree patterns of age, sex distribution, and morphologic characteristics, and that these tumors should be defined as belonging to the same entity [2,4]. Other reports suggest that cardia cancer is a distinct entity independent of subcardia cancer [1,8], and Kim et al found no significant differences in clinicopathological characteristics and protein expressions between Siewert types II and III carcinomas [10]. The prognosis has been reported to be significantly worse in cases of cardia carcinoma than in subcardia carcinomas [1,8,21], although Kim et al found no difference in survival rates between types II and III carcinomas [10].…”
Section: Discussionmentioning
confidence: 94%
“…Other reports suggest that cardia cancer is a distinct entity independent of subcardia cancer [1,8], and Kim et al found no significant differences in clinicopathological characteristics and protein expressions between Siewert types II and III carcinomas [10]. The prognosis has been reported to be significantly worse in cases of cardia carcinoma than in subcardia carcinomas [1,8,21], although Kim et al found no difference in survival rates between types II and III carcinomas [10]. The present study indicated that a poor prognosis for cardia carcinoma became distinct when type IIA tumors were analyzed separately from type IIB tumors.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation